(untitled) (Journal of Humanitarian and Applied Sciences, 2023)
Abstract: The issue of immigration to the Islamic Maghreb has become increasingly of interest to historians due to its important effects on the region. The Islamic Maghreb witnessed three major migrations, namely the migration of the Conquest, the migration of Bani Hilal, and the migration of the Andalusians to Morocco. These migrations resulted in several consequences and effects, including the emergence of the Maliki school of thought after the diversity of schools and their conflicts, as well as defining the region linguistically and Islamizing it forever. Migrations also contributed to the erasure of many countries, and in exchange for the emission of other countries, and emergence of political cities. Among the economic effects is the introduction of many agricultural and craft techniques following the migration of Andalusians to Morocco and the arrival of skilled craftsmen, hilalya migration also had a negative side from the economic point of view as they increased the deterioration of the region, although they do not bear responsibility for the sabotage and destruction of the region.